2004
DOI: 10.1007/s10884-004-7834-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth and Curvature on Pattern Formation

Abstract: Based on first principles, we derive a general model to describe the spatio-temporal dynamics of two morphogens. The diffusive part of the model incorporates the dynamics, growth and curvature of one-and two-dimensional domains embedded in R 3 . Our generalized diffusion process includes spatio-temporal varying diffusion coefficients, advection, and dilution terms. We present specific examples by analyzing a third order activator-inhibitor mechanism for the kinetic part. We carry out illustrative numerical sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
140
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 29 publications
3
140
1
2
Order By: Relevance
“…Firstly, we have shown that pattern initiation is in general sensitive to, and changes with, even slow domain growth. This is quite distinct from the commonly reported result that domain growth enhances the robustness of pattern selection (Plaza et al 2004). Nonetheless, despite its effects, slow domain growth will not prohibit the Turing mechanism as a means of driving a symmetry breaking bifurcation nor will slow domain growth induce oscillations at the bifurcation, as required for biological pattern.…”
Section: Discussion and Summarycontrasting
confidence: 81%
See 4 more Smart Citations
“…Firstly, we have shown that pattern initiation is in general sensitive to, and changes with, even slow domain growth. This is quite distinct from the commonly reported result that domain growth enhances the robustness of pattern selection (Plaza et al 2004). Nonetheless, despite its effects, slow domain growth will not prohibit the Turing mechanism as a means of driving a symmetry breaking bifurcation nor will slow domain growth induce oscillations at the bifurcation, as required for biological pattern.…”
Section: Discussion and Summarycontrasting
confidence: 81%
“…In most cases, as the first step in considering the Turing diffusively-driven instability analysis on growing domains, the reaction-diffusion equations (RDEs) are transformed into RDEs on fixed domains, but with time-dependence in the diffusion and dilution terms (Crampin et al 1999;Plaza et al 2004). These non-autonomous terms however typically invalidate standard linear stability analysis via plane wave decompositions, even with the common simplification that the domain growth is assumed to be isotropic.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 3 more Smart Citations